Sterically demanding pincer ligands for transition metal chemistry - Albelwe, Bayan L. (2025)
This work involves the development of new bulky ligands based on the carbazole framework to bind to a range of metals. The overall aim is to use these ligands to stabilise transition metal complexes that may prove useful in catalysis and small molecule activation. In this project, the novel ONO pincer pre-ligand 3,6-di-tert-butyl-1,8-bis(((triisopropylsilyl)oxy)methyl)-9H-carbazole 6 was synthesised and characterised by X-ray diffraction, NMR spectroscopy, mass spectrometry and elemental analysis. The bidentate imine ligands 1-phenyl-N-(pyridin-2-ylmethyl)methanimine 7 and [6-(methyl)-2-(iminophenylmethyl)pyridine] 8, known in the literature have been synthesised to further investigate their coordination chemistry. While 7 was not isolated successfully, X-ray crystallographic analysis revealed 7a, indicating the formation of a pyrazine ring under the reaction conditions used. The synthesis of 8 was confirmed by NMR spectroscopy and mass spectrometry.